A metrological approach to quantities that are counted and the unit one. (20th May 2021) - Brown, Richard J C
Abstract: There has long been debate over how to treat dimensionless quantities, or quantities with the unit one, within the International System of Units (SI). These arguments have been brought into sharper focus because of the increasing application of metrological principles in areas such as chemistry, biology and nanoscience where counting measurements are common. This has caused debates about how the SI should address counting quantities and the unit one (symbol 1). This article reviews the types of quantities with the unit one, how these quantities may be expressed together with their uncertainty and how this relates to counting. The qualities of counting quantities are explored in more detail and the range of possibilities for dealing with the unit one for counting are discussed. It is proposed that the SI should allow only the unit one for counting, but that downstream of the SI there may well be benefits from standardising the use of more descriptive, technical area specific 'units' for expressing the results of counting. As with all measurement it is essential that a full description, in words, of the counting quantity being expressed accompanies the measurement result.